Structure analysis of the water sector in Nuevo Leon and its intersectoral relations - Guajardo Quiroga, Ramón G.; García López, Patricia I. (Estudios Económicos de El Colegio de México, 2001)
This study traces the effect of water supply on output, employment and labor income in the Mexican state of Nuevo Leon. For this purpose, an input-output model with emphasis on the water sector is constructed. Firstly, water is isolated from electricity and gas as these utilities are recorded as a single sector. Secondly, water is disaggregated into four categories: drinking water, aquifers, sewage and treated wastewater. The results suggest that the water sector, particularly the provision of drinking water, has significant knock-on effects on the rest of the economy, which currently are sub estimated due to the lack of disaggregation.